1996
DOI: 10.1002/j.1460-2075.1996.tb01084.x
|View full text |Cite
|
Sign up to set email alerts
|

N-linked oligosaccharides are necessary and sufficient for association of glycosylated forms of bovine RNase with calnexin and calreticulin.

Abstract: Calnexin and calreticulin are lectin‐like molecular chaperones that promote folding and assembly of newly synthesized glycoproteins in the endoplasmic reticulum. While it is well established that they interact with substrate monoglucosylated N‐linked oligosaccharides, it has been proposed that they also interact with polypeptide moieties. To test this notion, glycosylated forms of bovine pancreatic ribonuclease (RNase) were translated in the presence of microsomes and their folding and association with calnexi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

11
87
2
2

Year Published

2000
2000
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 145 publications
(102 citation statements)
references
References 64 publications
11
87
2
2
Order By: Relevance
“…It is exceedingly unlikely that all of the examples of complexes between CNX or CRT with unglycosylated or nonglucose-trimmed proteins can be dismissed on the basis of their nonspecific inclusion in aggregates, trapping within detergent micelles, and insolubility of folding intermediates, as has frequently been claimed (1,(35)(36)(37). Indeed, in the present study, we have eliminated the possibilities of insolubility and aggregation through the use of high speed sedimentation and glycerol density gradient ultracentrifugation analyses.…”
Section: Calnexin Associates With Many Substrate Proteins When the Fomentioning
confidence: 76%
See 2 more Smart Citations
“…It is exceedingly unlikely that all of the examples of complexes between CNX or CRT with unglycosylated or nonglucose-trimmed proteins can be dismissed on the basis of their nonspecific inclusion in aggregates, trapping within detergent micelles, and insolubility of folding intermediates, as has frequently been claimed (1,(35)(36)(37). Indeed, in the present study, we have eliminated the possibilities of insolubility and aggregation through the use of high speed sedimentation and glycerol density gradient ultracentrifugation analyses.…”
Section: Calnexin Associates With Many Substrate Proteins When the Fomentioning
confidence: 76%
“…An increased affinity could result if CNX and CRT are oligomeric and capable of binding to multiple oligosaccharides on a glycoprotein substrate. Indeed there are several reports of enhanced CNX interactions when a glycoprotein is converted from a singly to a doubly glycosylated form (35,37,54). This could be due either to oligomeric CNX or to a bivalent CNX interaction that is induced by the precipitating anti-CNX antibody.…”
Section: Calnexin Associates With Many Substrate Proteins When the Fomentioning
confidence: 99%
See 1 more Smart Citation
“…The chain of glycan molecules is then biochemically modified within the ER and the Golgi apparatus to generate the diversified glycan moieties found in mature glycoproteins. ER ␣-glucosidases I and II are involved in the trimming of terminal glucose on core oligosaccharides, and the resulting monoglucosylated glycoproteins can bind to ER chaperones, the membrane-bound calnexin (CNX) and/or its soluble homologue calreticulin (CRT) (17,38,42). Removal of the last glucose from the glycans by glucosidase II releases the glycoprotein from CNX and/or CRT.…”
mentioning
confidence: 99%
“…It was originally believed that recognition and binding of monoglucosylated oligosaccharides present on glycoproteins were necessary and sufficient for calnexin and calreticulin to promote folding of the glycoproteins (see, for example, ref. 6). However, more recent experiments have indicated that both calnexin and calreticulin directly discriminate between protein conformational states, and that both proteins can function in vitro as chaperones for glycosylated, as well as nonglycosylated, substrates (7,8).…”
mentioning
confidence: 99%